A Comparative Analysis of Antimicrobial Property of Wine and Ozone with Calcium Hydroxide and Chlorhexidine - Anand, Shenbaga Kuttalam (J Clin Diagn Res, 2015)
BACKGROUND: The antibacterial properties of wine and ozone have been established but their antibacterial efficacies against endodontic pathogens are yet to be ascertained. AIM: The purpose of this study is to comparatively evaluate the antibacterial property of ozonated water, white wine (14%) and de-alcoholised white wine. MATERIALS AND METHODS: S.mutans and E.faecalis were subcultured and inoculated in a nutrient broth for 24 hours. The following groups were formulated: Group 1A:2% Chlorhexidine (Control group); Group 1B:White wine; Group 1C:Dealcoholised white wine; Group 1D:Ozonated water; Group 2A: Ca(OH)2 + Chlorhexidine (Control group); Group 2B: White wine + Ca(OH)2; Group 2C:De-alcoholised White wine + Ca(OH)2 + chlorhexidine; Group 2D:White wine + Ca(OH)2 + chlorhexidine and group 2E: Dealcoholised white wine + Ca(OH)2 + chlorhexidine. The samples were allowed to diffuse into the culture medium for two hours, later the S. mutans were streaked on to the blood agar medium and the E. faecalis were streaked on to the Muller Hilton agar medium and incubated for 48 hours at 370C the zone of inhibition was measured after 48 hours. RESULTS: There was no growth of microorganisms seen with ozonated water. Chlorhexidine showed large zone of inhibition compared to the other groups. White wine has better antimicrobial property than de-alcoholised white wine, but when mixed with calcium hydroxide the dealcoholised white wine has better action against the microorganisms. CONCLUSION: Ozonated water has the best antibacterial property and the antibacterial action of Calcium hydroxide is enhanced when it is mixed with de-alcoholised white wine.